Cognitive impairment in multiple sclerosis: An exploratory analysis of environmental and lifestyle risk factors - Amato, Maria Pia (PLoS One, 2019)
BACKGROUND: Many potentially modifiable risk factors for MS are investigated. It is not known, however, if these factors also apply to MS-related cognitive impairment (CI), a frequent consequence of MS. OBJECTIVE: The aim of our study was to assess risk factors for CI in MS patients, focusing on environmental exposures, lifestyle and comorbidities. METHODS: We included MS patients referring to MS Centers in Florence and Barletta between 2014 and 2017. Neuropsychological performance was assessed through the Rao’s battery and Stroop test, cognitive reserve (premorbid intelligence quotient–IQ) was evaluated using the National Adult Reading Test (NART). Potential risk factors were investigated through a semi-structured questionnaire. RESULTS: 150 patients were included. CI was detected in 45 (30%) subjects and was associated with older age (p<0.005), older age at MS onset (p = 0.016), higher EDSS score (p<0.005), progressive disease course (p = 0.048) and lower premorbid IQ score (p<0.005). As for risk factors, CI was related with lower physical activity in childhood-adolescence (p<0.005). In women, hormonal therapy resulted to be protective against CI (p = 0.041). However, in the multivariable analysis, the only significant predictors of CI were older age (p<0.05; OR 1.06, 95% CI 1.02–1.10) and lower premorbid IQ (p<0.05; OR 0.93, 95% CI: 0.88–0.98). Removing IQ from the model, CI was associated with higher EDSS (p = 0.030; OR 1.25, 95% CI 1.02–1.53) and, marginally, previous physical activity (p = 0.066; OR 0.49, 95% CI: 0.23–1.05) CONCLUSIONS: Our findings suggest that physical activity in childhood-adolescence could be a contributor to cognitive reserve building, thus representing a potential protective factors for MS-related CI susceptible to preventive strategies.